2015
DOI: 10.1111/eth.12386
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Group Personalities Characterise Consensus Decision‐Making in an Ant

Abstract: Non-human animals can exhibit idiosyncratic behaviour across individuals in much in the same way as humans. Animals with specific personalities may have advantages in some environments, and this idiosyncrasy may thus be of considerable ecological and evolutionary importance. In group-living organisms, personality can occur at the level of the group as well as that of the individual. However, at present, we have very little understanding of the possible benefits of group-level personality, and how this is linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…How these preferences are maintained within a group and how they affect the collective behavior are key questions for the understanding of the behavioral ecology of gregarious species. The presence of personalities within a group has been seen to have an important impact on the performance of the group during collective behaviors ( Brown and Irving 2014 , Cronin 2015 ). There is no doubt that such individual variability also influences collective fleeing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…How these preferences are maintained within a group and how they affect the collective behavior are key questions for the understanding of the behavioral ecology of gregarious species. The presence of personalities within a group has been seen to have an important impact on the performance of the group during collective behaviors ( Brown and Irving 2014 , Cronin 2015 ). There is no doubt that such individual variability also influences collective fleeing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Colony relocation represents one process that is regulated at both the group and individual level in social insects, and, indeed, wide variation exists among species in relation to how migration effort is assigned. Examples range from varying distributions of worker effort within colonies, as seen in the ant Myrmecina nipponica (Cronin, 2015), to extreme cases where a single individual is key to overall collective organisation, such as in the queenless Ponerine, Diacamma indicum (Sumana and Sona, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the three treatments were performed sequentially rather than randomly because of logistical limitations, and in some cases, colonies performed three emigrations. Previous studies of ant emigration have indicated that emigration performance may improve (faster emigrations) over replicated events, presumably because of a learning effect (Langridge et al., 2004), though this has not been found in other species (Cronin, 2015). We found no evidence of a learning effect, though cannot rule out the possibility that final emigrations (marked choice experiments) benefitted in some way from experience in earlier emigrations.…”
Section: Discussionmentioning
confidence: 94%